2017
DOI: 10.7150/ijms.17792
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the serum and liver proteomes in gut-microbiota-lacking mice

Abstract: Current nutrition research is focusing on health promotion, disease prevention, and performance improvement for individuals and communities around the world. The humans with required nutritional ingredients depend on both how well the individual is provided with balanced foods and what state of gut microbiota the host has. Studying the mutually beneficial relationships between gut microbiome and host is an increasing attention in biomedical science. The purpose of this study is to understand the role of gut mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
2
11
1
Order By: Relevance
“…It is noteworthy that previous reports have associated a decrease in MUP to be indicative of early liver tumor development [41,42]. It is further interesting to acknowledge that MUP-1 in germ-free mice has been found to be significantly decreased compared to conventional, specific pathogen free mice [43], which suggests that the expression of MUP-1 and other MUP family members may be regulated by the gut https://doi.org/10.1371/journal.pone.0234726.g003 Table 1. Statistics from the Kaplan Meir survival analysis of HCC specific genes leading to poor patient survival.…”
Section: Plos Onementioning
confidence: 79%
“…It is noteworthy that previous reports have associated a decrease in MUP to be indicative of early liver tumor development [41,42]. It is further interesting to acknowledge that MUP-1 in germ-free mice has been found to be significantly decreased compared to conventional, specific pathogen free mice [43], which suggests that the expression of MUP-1 and other MUP family members may be regulated by the gut https://doi.org/10.1371/journal.pone.0234726.g003 Table 1. Statistics from the Kaplan Meir survival analysis of HCC specific genes leading to poor patient survival.…”
Section: Plos Onementioning
confidence: 79%
“…In osteoblasts, it is critical for the suppression of androgen activity in osteoclastogenesis [ 38 ], but the Ar does not seem to suppress bone resorption through direct actions in osteoclasts [ 39 ]. Another study showed that the production of testosterone was reduced in GF mice [ 40 ]. In our study, the commensal microbiota may contribute to upregulation of androgen signaling by increasing Ar numbers in osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these studies suggest that the modulation of SCFA production by gut microbiota affects energy metabolism during exercise and hence contributes to exercise-induced adaptation. These products of microbiota fermentation can also be used as sources of energy in the liver and muscle cells to improve endurance performance by maintaining glycaemia over time [72,73].…”
Section: Effect Of Exercise On Gut Microbiota Metabolismmentioning
confidence: 99%